The naked diplomat understanding power and politics in the digital age - Fletcher, Tom. (London William Collins, 2017)
Who will be in power in the 21st century? Governments? Big business? Internet titans? And how do we influence the future?
Includes bibliographical references and index.
Keywords: Diplomacy